Aristolochic acid I promotes the invasion and migration of hepatocellular carcinoma cells by activating the C3a/C3aR complement system. (1st April 2023) - Li, Yu; Zhu, Sirui; Xue, Mei; Jing, Ye; Liu, Xiaoli; Cai, Danhong; Zhao, Ye; Bian, Yaoyao; Zhang, Zhaofeng; Zhang, Liang
Graphical abstract: Highlights: Aristolochic acid I promotes the motility of HCC cells. EMT is involved in aristolochic acid I-induced cell motility. Aristolochic acid I activates the C3a/C3aR system in HCC cells. The C3a/C3aR system plays a role in aristolochic acid I-induced HCC cell motility. Abstract: Aristolochic acid is an established human carcinogen. Previous reports have demonstrated a link between aristolochic acid exposure and liver cancer prevalence in Asia. The C3a/C3AR axis plays an essential role in regulating cancer cell migration and invasion. Here, we focused on the relationship between AA I-induced migration, invasion and epithelial-mesenchymal transition in HCC cells, as well as the possible role of the C3a/C3AR axis in these effects. HCC cells were exposed to different concentrations of AA I for 24 h. Cell migration and invasion abilities were evaluated with wound healing assays and Transwell invasion assays. The protein and mRNA expression levels were detected by western blot, immunofluorescence and quantitative real-time polymerase chain reaction (qRT-PCR) assays. Furthermore, the level of complement component C3a in the cell supernatant was determined by enzyme-linked immunosorbent assay. C3aRA, a C3a receptor antagonist, was used to block the C3a-C3aR axis. The results showed that aristolochic acid I promoted HCC cell invasion and migration. AAI exposure also induced EMT in HCC cells through E-cadherin downregulation and Snail, N-cadherin, and vimentin upregulation. AAI exposure increased the levels of secreted C3a and the expression of C3aR protein and mRNA in HCC cells. We further found that AA I-induced C3a/C3AR activation was involved in these effects. AA I-induced epithelial-to-mesenchymal transition (EMT), cell migration, and invasion were decreased by C3aR inhibition. Overall, our results suggest that AA I induces HCC cell migration and invasion through the EMT process, which is regulated by C3a/C3aR axis activation.